Quality of Life before and after Sleeve Gastrectomy in Lebanese Population - Marwan Alkassis; Fady Gh Haddad; Joseph Gharios; Roger Noun; Ghassan Chakhtoura (Journal of Obesity)
Introduction. Obesity is increasing worldwide and in Lebanon with a negative impact on the quality of life. The primary objective of this study is to measure the quality of life in obese subjects before and after bariatric surgery, depending on age, sex, and degree of weight loss. A secondary objective is to determine the impact of bariatric surgery on comorbidities associated with obesity. Materials and methods. Patients undergoing laparoscopic sleeve gastrectomy for BMI ≥ 30 kg/m2 between August 2016 and April 2017 were included. Participants completed the Moorehead-Ardelt Quality of Life Questionnaire II (MA II) prior to operation and one year after. Statistical analysis was carried out using SPSS statistics version 20.0. Results. 75 patients participated in the study. The majority were women (75%), and the mean age was 36.3 years. The mean weight loss was 36.57 kg (16–76). Initially, the total MA II score was −0.33 ± 0.93. Postoperatively, it increased to 1.68 ± 0.62 (p≤0.001). All MA II parameters improved after surgery (p≤0.001), but this improvement was independent of age and sex. Improvement in self-esteem, physical activity, work performance, and sexual pleasure was influenced by the degree of weight loss (p≤0.001). All comorbidities associated with obesity regressed significantly after sleeve gastrectomy (p<0.05) with the exception of gastroesophageal reflux and varicose veins of the lower limbs. Conclusion. Sleeve gastrectomy improves quality of life and allows reduction of comorbidities.